2013
DOI: 10.1590/s1984-29612013000100009
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological aspects ofLeishmania spp. in dogs in the Itaguai micro-region, Rio de Janeiro, Brazil

Abstract: This study evaluated factors associated with the frequency of Leishmania spp. antibodies in dogs residing in the Itaguai micro-region, State of Rio de Janeiro, Brazil. Blood samples were collected from 524 dogs. The serum samples were submitted to indirect fluorescent antibody test (IFAT) and enzyme-linked immunosorbent assay (ELISA) for Leishmania spp. The frequency of seropositive dogs was 28.24% (n = 148) in the micro-region, and among the three municipalities within that region, the highest frequency (p < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…The island, which belongs to the Armed Forces, prohibits the entry and exit of animals; therefore, we suspect that the cases of CVL may be indigenous. This prevalence is close to the findings by Silva et al (2013), who reported prevalence of 11.59% for CVL in Mangaratiba, Rio de Janeiro state. This finding corroborates Paranhos- Silva et al (1996), who carried out a cross-sectional study in Bahia state, and found prevalence of 23.5%.…”
Section: Discussionsupporting
confidence: 90%
“…The island, which belongs to the Armed Forces, prohibits the entry and exit of animals; therefore, we suspect that the cases of CVL may be indigenous. This prevalence is close to the findings by Silva et al (2013), who reported prevalence of 11.59% for CVL in Mangaratiba, Rio de Janeiro state. This finding corroborates Paranhos- Silva et al (1996), who carried out a cross-sectional study in Bahia state, and found prevalence of 23.5%.…”
Section: Discussionsupporting
confidence: 90%
“…Brazil is responsible by about 90% of VL cases, with the L. infantum species being the main parasite species responsible for the disease in dogs and humans [3]. Prophylactic measures have not been efficient to control this disease, and the available antileishmanial drugs present problems regarding their toxicity and/or high cost [4]. Therefore, the development of an effective vaccine could be considered as a strategy to control the spread of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The epidemiological data results are in agreement with those described in the literature (CRUZ et al, 2010;HUPPES et al, 2014;PEIXOTO et al, 2016). The marked prevalence of mixedbreed dogs has often been reported in similar studies (SILVA et al, 2013;ARAÚJO et al, 2016;PEIXOTO et al, 2016;PAULINO et al, 2018), and can be related to the greater prevalence of mixedbreed dogs among the stray population in Brazilian cities. As for age, only one patient was classified a geriatric, while the others were young or middleaged (of reproductive age).…”
Section: Resultsmentioning
confidence: 55%